To Partner or Not to Partner? The Partnership Between Platforms and Data Brokers in Two-Sided Markets - Zhang, Xin; Cheng, Lihong; Yu, Yugang; Tan, Yong (Information Systems Research, 2025)
Data have become a vital competitive asset for online advertising platforms, such as Facebook and Snapchat. These platforms often partner with data brokers to enhance targeting capabilities, which raises important consumer privacy concerns. This study develops a game-theoretic model to analyze the economic dynamics of partnerships between competing platforms and a data broker in a two-sided market. Our findings reveal that heightened consumer privacy concerns can encourage platforms to collaborate with data brokers rather than discourage them, as these concerns may strategically soften price competition on the advertiser side. However, when both platforms partner with a data broker, a prisoner’s dilemma may arise, even if the broker significantly improves targeting capabilities. From a policy perspective, such partnerships can harm consumer surplus in a purely ad-sponsored model, where users are not charged. Conversely, they may enhance consumer surplus in a mixed revenue model that combines advertising with subscriptions. These insights suggest that policymakers should consider regulations on platform-data broker partnerships to protect consumer interests, particularly regarding privacy protections that platforms may not prioritize under competitive pressures.